1999
DOI: 10.1007/s002449900524
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Particulate Lead via the Gills of Fish ( Carassius auratus )

Abstract: Carassius auratus were exposed to mixtures of constant free lead (0. 1 mg/L) and particulate lead (adsorbed on gibbsite particles) at varied concentrations (0, 0.4, 0.8, 1.2, 2.0, and 3.0 mg/L). The concentrations of lead and aluminum in the gills and intestines of the fish were determined after exposure. The gills were examined (after the exposure) with a light microscope for any particles adhering to the surface. The examination results revealed that lead accumulations on the gills increased with increased p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2000
2000
2005
2005

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 9 publications
1
17
0
1
Order By: Relevance
“…This research suggested that the particles adhered to the epithelial cell surface, with the desorption of copper occurring before the particles were sloughed o! the gill surface (Tao et al, 1999b). A similar process might be occurring in copper complexed with EDTA, diaminoethane, oxalic acid, or tartaric acid.…”
Section: Diwerences Among the Metals Complexed With The Various Liganmentioning
confidence: 97%
See 1 more Smart Citation
“…This research suggested that the particles adhered to the epithelial cell surface, with the desorption of copper occurring before the particles were sloughed o! the gill surface (Tao et al, 1999b). A similar process might be occurring in copper complexed with EDTA, diaminoethane, oxalic acid, or tartaric acid.…”
Section: Diwerences Among the Metals Complexed With The Various Liganmentioning
confidence: 97%
“…As a result, a mechanism for particulate metal uptake by the gills was suggested. The essential point of the proposed uptake mechanism was the desorption of the metal from the particles within the gill microenvironment in the area where the particles adhered to mucus (Tao et al, 1999b).…”
Section: Introductionmentioning
confidence: 99%
“…The 206 Pb/ 207 Pb and 208 Pb/ 207 Pb ratios in fish were significantly correlated (r 2 = 0.764), and those in shrimp and crab were not correlated (r 2 = 0.126). Fish can bioaccumulate particle Pb through their gills (Tao et al, 1999). As fishes are more mobile in water columns, they are likely to be more exposed to weakly soluble and potentially bioavailable Pb originating from anthropogenic atmospheric depositions and/or from the inputs derived from the discharges of wastewater.…”
Section: Stable Pb Isotope Compositions In Aquatic Organismsmentioning
confidence: 99%
“…It was observed that although kaolin clay could reduce "sh uptake of copper, the results of stoichiometric analysis indicated that a fraction of the kaolin clay-adsorbed copper might be available for "sh uptake via gills (Tao et al, 1999a, Liang et al, 1999. Similar phenomena on particulate lead uptake by gold"sh (Carassius auratus) was reported (Tao et al, 1999b).…”
Section: Introductionmentioning
confidence: 54%
“…It was reported that after exposure to copper adsorbed on kaolin clay (0}182 mg/L), the copper accumulated in the gills of neon tetras (Paracheirodon innesi) (Tao et al, 1999a). Similarly, elevated lead content was observed in the gills of gold"sh (Carassius auratus) exposed to varied concentrations of particulate lead (0, 0.4, 0.8, 1.2, 2.0, and 3.0 mg/L) adsorbed on gibbsite particles (Tao et al, 1999b). For both copper and lead, the accumulation in the "sh gills increased almost linearly with the increase in particulate copper or lead content in the water.…”
Section: Uptake Of Particulate Cadmium By Fish Gillsmentioning
confidence: 83%